Depression, family support and hopelessness: a correlated study - Baptista, Makilim Nunes; Carneiro, Adriana Munhoz; Cardoso, Hugo Ferrari [UNESP] (My University, 2014)
This study aimed to verify the relationship between depression, hopelessness and family support. to this aim, were applied the Escala Baptista de Depressão-Adulto EBADEP- A, The Beck Hopelessness Scale –BHS, Inventário de Percepção de Suporte Familiar- IPSF and a sociodemographic questionnaire on a sample of 198 undergraduate of Pharmacy and Psychology courses of a particular university at São Paulo state (Brazil) with mean age of 23.44 years (SD = 6.8), and with a prevalence of women (80.7%). Results showed significant and positive correlations between EBADEP- A and BHS and significant and negative correlations between EBADEP- A/ BHS and IPSF, indicating that the higher perception of family support the fewer depressive symptoms and hopelessness, agreeing with literature.

El presente estudio buscó verificar la asociación de la depresión, desesperanza y el apoyo familiar. Con este fin, se aplicó la Escala Baptista de Depressão versión para adultos- EBADEP- A, Escala de Desesperanza de Beck, BHS, el Inventario de Percepção de Suporte Familiar - IPSF y un cuestionario socio-demográfico en una muestra de 198 estudiantes de Farmacia y Psicología en una universidad privada en el Estado de São Paulo (Brasil), con el promedio de edad de 23.44 años (DE= 6.8) y de las mujeres (80.7 %). Los resultados indicaron una correlación positiva y significativa entre BHS y EBADEP- A y negativa y significativa entre EBADEP- A y BHS con IPSF, lo que sugiere que cuanto mayor es la percepción del apoyo familiar, menos síntomas depresivos y la desesperanza, que muestran que los resultados son consistentes con la literatura.
Depressión, apoyo familiar y desesperanza: un estudio de correlación
Keywords: Depressive symptoms; Hopelessness; Family; Psychological assessment; Síntomas depresivos; Desesperanza; Familia; Evaluación psicológica